1997
DOI: 10.1111/j.1432-1033.1997.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Increases Expression of 5‐Lipoxygenase and its Activating Protein in Human Monocytes and THP‐1 Cells

Abstract: The aim of this study was to assess the effect of dexamethasone on 5-lipoxygenase pathway expression in human peripheral blood monocytes and the acute monocytic leukemia cell line, THP-I. Cells were conditioned over a period of days with dexamethasone, at concentrations relevant in vivo, to study the effect of the glucocorticoid on calcium-ionophore-stimulated 5-lipoxygenase product and arachidonic acid release. The effect of dexamethasone on levels of immunoreactive protein and steady-state messenger RNA enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 47 publications
(19 reference statements)
9
53
1
1
Order By: Relevance
“…However, Sebaldt et al (49) previously reported that a high dose of glucocorticoids (60 mg prednisone/day) was required to inhibit leukotriene synthesis in macrophage-rich BALF recovered from human subjects. In addition, Riddick et al (50) have shown that pretreatment of monocytes with dexamethasone, at physiologic levels, actually increased calcium-ionophore-stimulated leukotriene synthesis. Finally, we were able to demonstrate that exogenous leptin, at a very high dose, completely restored macrophage leukotriene synthesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sebaldt et al (49) previously reported that a high dose of glucocorticoids (60 mg prednisone/day) was required to inhibit leukotriene synthesis in macrophage-rich BALF recovered from human subjects. In addition, Riddick et al (50) have shown that pretreatment of monocytes with dexamethasone, at physiologic levels, actually increased calcium-ionophore-stimulated leukotriene synthesis. Finally, we were able to demonstrate that exogenous leptin, at a very high dose, completely restored macrophage leukotriene synthesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Mild stress levels of corticosterone are even more effective than high stress levels in augmenting excitotoxininduced expression of TNF-α and iNOS in vitro and in vivo (MacPherson et al 2005;Munhoz in prep). Dexamethasone causes a dose-and time-dependent increase in expression and activity of prostaglandin D2 synthase in neuronal cultures (Garcia-Fernandez et al 2000) and dexamethasone or corticosterone treatment increases the pro-inflammatory leukotriene synthesis enzyme 5-lipoxygenase in both the hippocampus (Uz et al 1999) and macrophages (Riddick et al 1997). Finally, dexamethasone alone or more robustly in conjunction with retinoic acid, causes increased COX-1 expression in neuroblastoma cell lines (Schneider et al 2001).…”
Section: 3mentioning
confidence: 99%
“…The reasons for the ineffectiveness of glucocorticosteroids as inhibitors of leukotriene formation in vivo are not established. At least in vitro, glucocorticosteroid treatment has been found to increase the expression of 5-lipoxygenase and FLAP [182,83]. Obviously, the effects of glucocorticosteroids on cell traffic and activation or expression of cytokines and different enzymes may affect leukotriene production indirectly, but the phospholipases involved in leukotriene synthesis in humans are apparently glucocorticosteroid-insensitive in vivo.…”
Section: Pharmacological Control Of the Leukotriene Pathwaymentioning
confidence: 99%